Inositol lipids: from an archaeal origin to phosphatidylinositol 3, 5‐bisphosphate faults in human disease. (3rd September 2013) - Michell, Robert H.
<x xml:space="preserve">Abstract</x> The last couple of decades have seen an extraordinary transformation in our knowledge and understanding of the multifarious biological roles of inositol phospholipids. Herein, I briefly consider two topics. The first is the role that recently acquired biochemical and genomic information – especially from archaeons – has played in illuminating the possible evolutionary origins of the biological employment of inositol in lipids, and some questions that these studies raise about the 'classical' biosynthetic route to phosphatidylinositol. The second is the growing recognition of the importance in eukaryotic cells of phosphatidylinositol 3, 5‐bisphosphate. Phosphatidylinositol 3, 5‐bisphosphate only entered our phosphoinositide consciousness quite recently, but it is speedily gathering a plethora of roles in diverse cellular processes and diseases thereof. These include: control of endolysosomal vesicular trafficking and of the activity of ion channels and pumps in the endolysosomal compartment; control of constitutive and stimulated protein traffic to and from plasma membrane subdomains; control of the nutrient and stress‐sensing target of rapamycin complex 1 pathway (TORC1); and regulation of key genes in some central metabolic pathways.